Recruiting Testicular Torsion Introduces an Azoospermic Mouse Model for Spermatogonial Stem Cell Transplantation - Azizollahi, Saeid; Aflatoonian, Reza; Sedigi-Gilani, Mohamad Ali; Asghari Jafarabadi, Mohamad; Behnam, Babak; Azizollahi, Gholamabbas; Koruji, Morteza (Urology Journal, 2014)
Abstract Purpose: To investigate the long-term effect of testicular torsion on sperm parameters and testis structure in order to introduce a novel mice azoospermic model for spermatogonial stem cell transplantation. Materials and Methods: Unilateral testicular torsion was created. The animals were divided into two groups each containing 15 mice. They underwent 2 and 4 hours of unilateral testicular ischemia, respectively. All animals in this experiment were aged matched. The experimental (n = 5) groups were studied 2, 4 and 10 weeks after testicular ischemia reperfusion. Moreover, the left testes and epididymis were removed for sperm analysis and for weight and histopathological evaluation. Finally isolated spermatogonial stem cells were transplanted in the testes that underwent 2 hours of ischemia reperfusion, two weeks post-surgery. Results: All the investigated parameters demonstrated a sharp decline at 2, 4 and 10 weeks after testicular torsion, whereas 2-hour ischemia was found to be less injurious in testicular tissue structure. Two months after xenotransplantation, the transplanted cells were localized in the basal of the seminiferous tubules of the recipient ischemic testes. Conclusion: Torsion can cause permanent azoospermia in mouse. Also Testicular torsion 2 weeks after the 2 hours ischemia reperfusion may prove useful for recipient preparation for SSCs transplantation in mouse. <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Arial; mso-bidi-theme-font:minor-bidi;} > <! [endif] > Purpose: Testicular torsion is a urological emergency disorder in which an affected testicle tends toward ischemia and reproductive system dysfunction. The purposes of this study were to investigate the long-term effect of testicular torsion on sperm parameters, testis structure and assessment of stem cell niche alterations by spermatogonial stem cell (SSC) transplantation. Methods: Unilateral testicular torsion was created by twisting the left testis 720? in a counterclockwise direction and maintained by fixing the testis to the scrotum. The animals were divided into two groups each containing 15 mice .They underwent 2 and 4 hours of unilateral testicular ischemia, respectively. All animals in this experiment were aged matched. The experimental groups were studied 2, 4 and 10 weeks after testicular ischemia reperfusion. Moreover, the left testes and epididymides were removed for sperm analysis and for weight and histopathological evaluation. Finally isolated SSCs were transplanted in the testes that underwent 2 hours of ischemia reperfusion, two weeks post-surgery. Results: All the investigated parameters demonstrated a sharp decline at 2, 4 and 10 weeks after testicular torsion, whereas 2-hour ischemia was found to be less injurious in testicular tissue structure. Two months after xenotransplantation, the transplanted cells were localized in the basal of the seminiferous tubules of the recipient ischemic testes. Conclusions: Torsion can cause permanent azoospermia in mouse and this effect is irreversible after 10 weeks. Also Testicular torsion 2 weeks after the 2 hours ischemia reperfusion may prove useful for recipient preparation For SSCs transplantation in mouse. Key words: testicular torsion, </bo-->